Phase change insulating film, preparation method thereof and liquid cooling plate
By using the phase change insulation film prepared by the phase change packaging coating liquid, the problems of brittleness and environmental pollution of the liquid-cooled plate insulation film are solved, and efficient insulation and phase change heat storage functions are achieved, which are suitable for thermal management of lithium batteries.
Patent Information
- Application Number
- CN202411542721.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
The insulating film materials of existing liquid-cooled plates are highly brittle and lack phase change characteristics. They are prone to cracking under external forces, resulting in insulation failure, and the spraying process is complex and environmental pollution is serious.
Using phase change encapsulation coating liquid, including epoxy resin, multifunctional glycidyl ether diluent, curing agent, accelerator, coupling agent, oil absorbing filler, thermal conductivity filler and phase change material, curing by coating and drying A phase change insulating film was prepared and attached to the surface of the liquid-cooled plate.
It provides an insulating film with excellent bonding, insulation, heat conduction, flame retardant and phase change heat storage functions, which improves the insulation properties of liquid-cooled plates and phase change heat absorption capabilities, and is suitable for the heat-expressing management of lithium batteries.
Smart Images

Figure BDA0005113140320000091 
Figure BDA0005113140320000101 
Figure BDA0005113140320000102
Abstract
Description
Technical Field
[0001] The present invention relates to the field of packaging materials, and in particular to a phase change insulating film, a preparation method thereof and a liquid cooling plate. Background Art
[0002] As an important component of battery thermal management, the power battery liquid cooling plate is responsible for providing a relatively comfortable operating environment for the battery to avoid damage to the battery caused by overheating or overcooling. The liquid cooling plate is mainly made of aluminum alloy and needs to be close to the battery when in use, so proper insulation treatment must be performed to ensure the safety of the entire vehicle. The current treatment solution is to spray a layer of epoxy resin coating on the surface of the liquid cooling plate. Epoxy resin has good adhesion and good insulation properties.
[0003] Phase change material, as a material that can absorb heat at a constant temperature during the phase change process and has large latent heat performance, has great application prospects in temperature-sensitive fields such as battery thermal management.
[0004] At present, the insulating film used for liquid cooling plates is mostly made of epoxy resin. The disadvantages of epoxy resin are that it is brittle and has no phase change characteristics. It is easy to crack under external forces, resulting in insulation failure. In addition, the spraying construction process is complicated and requires a large amount of solvent dilution, causing environmental pollution.
[0005] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a phase change insulating film, a preparation method thereof and a liquid cooling plate in view of the deficiencies in the above-mentioned prior art.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a phase change insulating film is provided, which is obtained by coating, drying and curing a phase change encapsulation coating liquid, wherein the phase change encapsulation coating liquid includes the following raw material components in parts by weight: 30-50 parts of epoxy resin, 1-20 parts of multifunctional glycidyl ether diluent, 3-5.5 parts of curing agent, 0.05-0.2 parts of accelerator, 0.05-0.2 parts of coupling agent, 20-30 parts of oil-absorbing filler, 5-15 parts of thermal conductive filler, 15-25 parts of phase change material, and 0.5-2 parts of flame retardant.
[0008] Preferably, the epoxy resin is at least one selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, distyrene epoxy resin, biphenyl epoxy resin, polyether modified epoxy resin, and polyurethane modified epoxy resin.
[0009] Preferably, the multifunctional glycidyl ether diluent is at least one selected from benzyl glycidyl ether, phenyl glycidyl ether, polyethylene glycol glycidyl ether, and polypropylene glycol glycidyl ether.
[0010] Preferably, the oil-absorbing filler is in powder or granular form, and its material is one or more of graphite, expanded graphite, graphene, graphene oxide, carbon nanotubes, and silicon carbide;
[0011] The thermal conductive filler is one or a mixture of magnesium oxide, beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, crystalline silicon dioxide, and silicon carbide;
[0012] The phase change material is one or more of paraffin, organic acid and sugar alcohol.
[0013] Preferably, the curing agent is any one of a latent amine curing agent, a phenolic curing agent and an acid anhydride curing agent or a mixture of at least two thereof; the latent amine curing agent is any one of dicyandiamide, aromatic amine, diaminodiphenylmethane and diaminodiphenyl sulfone or a mixture of at least two thereof; the acid anhydride curing agent is an acid anhydride having an aromatic skeleton and a hydride or modified product thereof and / or an acid anhydride having an alicyclic skeleton and a hydride or modified product thereof;
[0014] The accelerator is any one of urea derivatives, imidazole and its derivatives, acetylacetone metal salts, triorganophosphine compounds, quaternary ammonium salts and fluoroborates, or a mixture of at least two of them; the urea derivative is any one of 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-p-nitrophenyl-1,1-dimethylurea, N-(3,4-dichlorophenyl)-N,N′-diphenylurea, 4-phenyl-1,1-dimethylaminourea, or a mixture of at least two of them.
[0015] Preferably, the coupling agent is any one of a titanate coupling agent, an aluminate coupling agent, an organosilane coupling agent, an organochromium coupling agent and a borate coupling agent, or a mixture of at least two thereof;
[0016] The titanate coupling agent is any one of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, 3-glycidyloxypropyl trimethoxy silane (KBM-403), isopropyl tris(dioctyl phosphate acyloxy) titanate, isopropyl dioleyloxy (dioctyl phosphate acyloxy) titanate, monoalkoxy unsaturated fatty acid titanate, bis(dioctyl pyrophosphate) ethylene titanate and triethanolamine chelate, bis(dioctyl pyrophosphate) ethylene titanate, γ-glycidyloxypropyl trimethoxy silane (KH-560) or a mixture of at least two thereof;
[0017] The flame retardant is any one of a phosphorus flame retardant, a nitrogen flame retardant, a silicon flame retardant, a metal hydroxide flame retardant, a metal oxide flame retardant and a metal boride flame retardant, or a mixture of at least two thereof;
[0018] The phosphorus-based flame retardant is any one of an organic phosphide, an organic phosphonate and a phosphite, or a mixture of at least two thereof;
[0019] The organic phosphonate is any one of condensation-type halogen-free phosphate, tricresyl phosphate, triphenyl phosphate, tricresyl phosphate, butylbenzene phosphate, propylbenzene phosphate, phenoxy polyphosphazene, dimethyl methylphosphonate, diethyl ethylphosphonate, isopropylphenyl phosphate, tert-butylbenzene diyl phosphate, tetraarylarylene bisphosphate, resorcinol phosphate, tetraphenyl bisphenol A-diphosphate and pentaerythritol melamine phosphate, or a mixture of at least two thereof.
[0020] A second aspect of the present invention provides a method for preparing the phase change insulating film as described above, comprising the following steps:
[0021] 1) adding the phase change material into a container, heating it to 80-100° C., adding the oil-absorbing filler under stirring, mixing evenly, then cooling it to room temperature, and then ball-milling the resulting mixture to obtain an intermediate composite material;
[0022] 2) adding epoxy resin, multifunctional glycidyl ether diluent, thermal conductive filler, coupling agent, curing agent, accelerator and flame retardant into the solvent and mixing evenly to obtain a support layer material;
[0023] 3) adding the intermediate composite material to the supporting layer material and stirring evenly to obtain a phase change encapsulation coating liquid;
[0024] 4) The phase change encapsulation coating liquid is applied to the surface of the substrate layer, and heated and dried at 70-100° C. for 2-10 minutes, and a release film is attached to the surface of the formed phase change adhesive film to obtain the phase change insulating film.
[0025] More preferably, the method for preparing the phase change insulating film comprises the following steps:
[0026] 1) adding the phase change material into a container, heating it to 90° C., adding the oil-absorbing filler under stirring, mixing evenly, then cooling it to room temperature, and then ball-milling the obtained mixture to obtain an intermediate composite material;
[0027] 2) adding epoxy resin, multifunctional glycidyl ether diluent, thermal conductive filler, coupling agent, curing agent, accelerator and flame retardant into the solvent and mixing evenly to obtain a support layer material;
[0028] 3) adding the intermediate composite material to the supporting layer material and stirring evenly to obtain a phase change encapsulation coating liquid;
[0029] 4) The phase change encapsulation coating liquid is applied to the surface of the polyimide substrate layer with a thickness of 100 μm, and the layer is heated and dried at 90° C. for 5 min. A release film is attached to the surface of the formed phase change adhesive film to obtain the phase change insulating film.
[0030] Preferably, the oil-absorbing filler is expanded graphite, which is pretreated with a coupling agent KH560 before use, and the pretreatment method is: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and stirred for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added, stirred for 3 hours, and then vacuum filtered, and dried in an oven at 100°C for 2 hours to obtain pretreated graphite and boron nitride materials;
[0031] The thermal conductive filler is boron nitride, which is pretreated with a coupling agent KH560 before use. The pretreatment method is as follows: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and stirred continuously for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added, stirred for 3 hours, and then vacuum filtered, and dried in an oven at 100°C for 2 hours to obtain pretreated graphite and boron nitride materials;
[0032] Preferably, the epoxy resin is E44 bisphenol A epoxy resin, the multifunctional glycidyl ether resin diluent is polypropylene glycol glycidyl ether, the curing agent is dicyandiamide, the accelerator is imidazole, the coupling agent is KH560, the phase change material is paraffin, and the flame retardant is triphenyl phosphate.
[0033] Preferably, the solvent is toluene, ethyl acetate, butanone or a mixture of at least two thereof.
[0034] The third aspect of the present invention provides a liquid cooling plate, which is prepared by the following method: tearing off the release film on the phase change insulating film prepared by the method as described above, and then using a 100°C hot stick to adhere the phase change adhesive film to the surface of the water cooling plate at 0.1-0.5MPa, and baking it in an oven at 180°C for 30 minutes to obtain the liquid cooling plate.
[0035] The beneficial effects of the present invention are:
[0036] The present invention provides a phase change insulating film, a preparation method thereof and a liquid cooling plate using the phase change insulating film. The phase change insulating film of the present invention has excellent adhesion, insulation, thermal conductivity, flame retardancy and phase change heat storage function. On the one hand, it can be used as an insulating treatment for a liquid cooling plate. On the other hand, it has certain thermal conductivity and phase change heat storage. In the heat release process of lithium battery charging and discharging, it can absorb part of the heat to replace part of the water cooling plate. When the battery releases heat, it can absorb part of the energy to play a heat preservation role in a low temperature state. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0038] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0039] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0040] The present invention provides a phase change insulating film, which is obtained by coating, drying and curing a phase change encapsulation coating liquid, wherein the phase change encapsulation coating liquid comprises the following raw material components in parts by weight: 30-50 parts of epoxy resin, 1-20 parts of multifunctional glycidyl ether diluent, 3-5.5 parts of curing agent, 0.05-0.2 parts of accelerator, 0.05-0.2 parts of coupling agent, 20-30 parts of oil-absorbing filler, 5-15 parts of thermal conductive filler, 15-25 parts of phase change material, and 0.5-2 parts of flame retardant.
[0041] In a preferred embodiment, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, distyrene epoxy resin, biphenyl epoxy resin, polyether modified epoxy resin, and polyurethane modified epoxy resin. More preferably, it is one or two of bisphenol A epoxy resin / bisphenol F epoxy resin, such as epoxy resins such as E51, E44, E20, and EP128.
[0042] In a preferred embodiment, the multifunctional glycidyl ether diluent is selected from at least one of benzyl glycidyl ether, phenyl glycidyl ether, polyethylene glycol glycidyl ether, and polypropylene glycol glycidyl ether. More preferably, the diluent has a toughening effect, such as polyethylene glycol glycidyl ether, polypropylene glycol glycidyl ether, or a mixture of two thereof.
[0043] In a preferred embodiment, the oil-absorbing filler is in powder or granular form, and its material is one or more of graphite, expanded graphite, graphene, graphene oxide, carbon nanotubes, and silicon carbide. More preferably, it is graphite, expanded graphite, graphene, or graphene oxide, and the particle size of graphite, expanded graphite, graphene, or graphene oxide is 50 to 200 meshes, and the expansion multiple of expanded graphite is 50 to 200 times.
[0044] In a preferred embodiment, the thermally conductive filler is a mixture of one or more of magnesium oxide, beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, crystalline silicon dioxide, and silicon carbide. Alumina is further preferred. The shape of the thermally conductive filler is one or more of polygonal, spherical, spherical, lamellar, and blocky. It is further preferred to be spherical or spherical because spherical fillers have better filling properties and high thermal conductivity. Of course, the main part is spherical or spherical, and it is also possible to fill some fillers of other shapes, which also saves costs. Preferably, the average particle size of the thermally conductive filler is 0.1 to 60 μm, and more preferably 0.1 to 5 μm.
[0045] In a preferred embodiment, the phase change material is an organic phase change material, such as higher aliphatic hydrocarbons, fatty acids and stearic acid, palmitic acid, polyethylene glycol, etc., for example, specifically paraffin, organic acid and sugar alcohol, etc. Further preferably, the phase change material is paraffin with a phase change temperature of -21°C to 120°C, and further preferably, it is paraffin with a phase change temperature of 58°C.
[0046] In a preferred embodiment, the curing agent is any one of a latent amine curing agent, a phenolic curing agent and an acid anhydride curing agent, or a mixture of at least two of them. Further, the latent amine curing agent is any one of dicyandiamide, aromatic amine, diaminodiphenylmethane and diaminodiphenyl sulfone, or a mixture of at least two of them, and the acid anhydride curing agent is an acid anhydride having an aromatic skeleton and its hydride or modified product and / or an acid anhydride having an alicyclic skeleton and its hydride or modified product.
[0047] In a preferred embodiment, the accelerator is any one of urea derivatives, imidazole and its derivatives, acetylacetonate metal salts, triorganophosphine compounds, quaternary ammonium salts and fluoroborates, or a mixture of at least two thereof; the urea derivative is any one of 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-p-nitrophenyl-1,1-dimethylurea, N-(3,4-dichlorophenyl)-N,N′-diphenylurea, 4-phenyl-1,1-dimethylaminourea, or a mixture of at least two thereof.
[0048] In a preferred embodiment, the coupling agent is any one of a titanate coupling agent, an aluminate coupling agent, an organosilane coupling agent, an organic chromium coupling agent and a borate coupling agent, or a mixture of at least two thereof. Further, the titanate coupling agent is any one of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, 3-glycidyloxypropyl trimethoxysilane (KBM-403), isopropyl tri(dioctyl phosphate acyloxy) titanate, isopropyl dioleyloxy (dioctyl phosphate acyloxy) titanate, monoalkoxy unsaturated fatty acid titanate, a chelate of bis(dioctyl pyrophosphate ester) ethylene titanate and triethanolamine, bis(dioctyl pyrophosphate ester) ethylene titanate, or a mixture of at least two thereof.
[0049] In a preferred embodiment, the flame retardant is any one of a phosphorus flame retardant, a nitrogen flame retardant, a silicon flame retardant, a metal hydroxide flame retardant, a metal oxide flame retardant and a metal boride flame retardant, or a mixture of at least two thereof.
[0050] Further, the phosphorus-based flame retardant is any one or a mixture of at least two of an organic phosphide, an organic phosphonate, and a phosphite;
[0051] The organic phosphonate is any one of condensation-type halogen-free phosphate, tricresyl phosphate, triphenyl phosphate, tricresyl phosphate, butylbenzene phosphate, propylbenzene phosphate, phenoxy polyphosphazene, dimethyl methylphosphonate, diethyl ethylphosphonate, isopropylphenyl phosphate, tert-butylbenzene diyl phosphate, tetraarylarylene bisphosphate, resorcinol phosphate, tetraphenyl bisphenol A-diphosphate and pentaerythritol melamine phosphate, or a mixture of at least two thereof.
[0052] The present invention also provides a method for preparing the above phase change insulating film, comprising the following steps:
[0053] 1) adding the phase change material into a container, heating it to 80-100° C., adding the oil-absorbing filler under stirring, mixing evenly, then cooling it to room temperature, and then ball-milling the resulting mixture to obtain an intermediate composite material;
[0054] 2) adding epoxy resin, multifunctional glycidyl ether diluent, thermal conductive filler, coupling agent, curing agent, accelerator and flame retardant into the solvent and mixing evenly to obtain a support layer material;
[0055] 3) adding the intermediate composite material to the supporting layer material and stirring evenly to obtain a phase change encapsulation coating liquid;
[0056] 4) Applying the phase change encapsulation coating liquid to the surface of the substrate layer, heating and drying at 70-100° C. for 2-10 minutes, and attaching a release film to the surface of the formed phase change adhesive film to obtain a phase change insulating film.
[0057] Among them, the thickness of the phase change film is 0.025mm-0.1mm.
[0058] In a more preferred embodiment, the method for preparing the phase change insulating film comprises the following steps:
[0059] 1) adding the phase change material into a container, heating it to 90° C., adding the oil-absorbing filler under stirring, mixing evenly, then cooling it to room temperature, and then ball-milling the obtained mixture to obtain an intermediate composite material;
[0060] 2) adding epoxy resin, multifunctional glycidyl ether diluent, thermal conductive filler, coupling agent, curing agent, accelerator and flame retardant into the solvent and mixing evenly to obtain a support layer material;
[0061] 3) adding the intermediate composite material to the supporting layer material and stirring evenly to obtain a phase change encapsulation coating liquid;
[0062] 4) The phase change encapsulation coating liquid is applied to the surface of the polyimide substrate layer with a thickness of 100 μm, and the layer is heated and dried at 90° C. for 5 min. A release film is attached to the surface of the formed phase change adhesive film to obtain a phase change insulating film.
[0063] In a preferred embodiment, the oil-absorbing filler is expanded graphite, which is pretreated with a coupling agent KH560 before use. The pretreatment method is: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and continuously stirred for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added. After stirring for 3 hours, vacuum filtration is performed and the mixture is dried in an oven at 100°C for 2 hours to obtain pretreated graphite and boron nitride materials.
[0064] In a preferred embodiment, the thermal conductive filler is boron nitride, which is pretreated with a coupling agent KH560 before use. The pretreatment method is: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and stirred continuously for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added. After stirring for 3 hours, vacuum filtration is performed and the mixture is dried in an oven at 100°C for 2 hours to obtain pretreated graphite and boron nitride materials.
[0065] In a preferred embodiment, the epoxy resin is E44 bisphenol A epoxy resin, the multifunctional glycidyl ether resin diluent is polypropylene glycol glycidyl ether, the curing agent is dicyandiamide, the accelerator is imidazole, the coupling agent is KH560, the phase change material is paraffin, and the flame retardant is triphenyl phosphate.
[0066] In a preferred embodiment, the solvent is toluene, ethyl acetate, butanone or a mixture of at least two thereof.
[0067] The present invention also provides a liquid cooling plate, which is prepared by the following method: tearing off the release film on the phase change insulating film prepared by the above method, and then using a 100°C hot stick to adhere the phase change adhesive film to the surface of the water cooling plate at 0.1-0.5MPa, and baking it in a 180°C oven for 30 minutes to obtain a liquid cooling plate.
[0068] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0069] The sources of the main raw materials in the following examples and comparative examples are described as follows:
[0070] Bisphenol A epoxy resin E44 was purchased from Wuxi Changgan Chemical, polypropylene glycol glycidyl ether was purchased from Jinan Yunuo Chemical Co., Ltd., paraffin was purchased from Foshan Hongsheng Chemical Co., Ltd., dicyandiamide was purchased from Shandong Zhongwei New Materials Co., Ltd., imidazole was purchased from Shandong Yunding Chemical Co., Ltd., triphenyl phosphate Dongguan Changhe Chemical Co., Ltd., expanded graphite was purchased from Shanghai Youmo Composite Materials Co., Ltd., and butanone was purchased from Shanghai Aladdin Reagent.
[0071] The following examples and comparative examples all provide the same preparation method of phase change insulating film products, the only difference being the specific formula ratio of the phase change encapsulation coating liquid (see Table 1 and Table 2 below for details), the units of the distribution ratio of each component are all parts by weight, and the amount of butanone added as the formula solvent is 50 parts by weight. The specific preparation method is as follows:
[0072] 1) adding the phase change material into a container, heating it to 90° C., adding the oil-absorbing filler under stirring, mixing evenly, then cooling it to room temperature, and then ball-milling the obtained mixture to obtain a granular intermediate composite material;
[0073] The oil-absorbing filler is expanded graphite, which is pretreated with a coupling agent KH560 before use. The pretreatment method is as follows: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and continuously stirred for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added, stirred for 3 hours, and then vacuum filtered, and dried in a 100°C oven for 2 hours to obtain pretreated graphite and boron nitride materials;
[0074] 2) adding epoxy resin, multifunctional glycidyl ether diluent, thermal conductive filler, coupling agent, curing agent, accelerator and flame retardant into the solvent and mixing evenly to obtain a support layer material;
[0075] The thermal conductive filler is boron nitride, which is pretreated with a coupling agent KH560 before use. The pretreatment method is as follows: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and stirred continuously for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added, stirred for 3 hours, and then vacuum filtered, and dried in an oven at 100°C for 2 hours to obtain pretreated graphite and boron nitride materials;
[0076] 3) adding the intermediate composite material to the supporting layer material and stirring evenly to obtain a phase change encapsulation coating liquid;
[0077] 4) The phase change encapsulation coating liquid is applied to the surface of the polyimide substrate layer with a thickness of 100 μm, and heated and dried at 90° C. for 5 min. A release film is attached to the surface of the formed phase change adhesive film with a thickness of 0.03 mm to obtain a phase change insulating film.
[0078] The following performance tests were performed on the phase change insulating films prepared in the examples and comparative examples:
[0079] 1.180° peel strength test: The prepared sample was cut into 25.4mm wide and 100mm long. After standing for 20 minutes, the peel strength (N / 25mm) on the water-cooled plate was tested.
[0080] 2. Heat resistance: The prepared phase change liquid cold plate insulation film was placed in an oven at 130°C and heated for 15 days. Judgment criteria: whether bubbles, leakage, stratification, bubbling, etc. appeared after heating for 15 days. Results: Excellent: no bubbling, stratification, or leakage. Poor: leakage and stratification
[0081] 3. Breakdown voltage: Cut the phase change film sample into 10cm*10cm and use a breakdown voltage tester to test the breakdown voltage (KV).
[0082] 4. Thermal conductivity test: The phase change film is punched into samples with a diameter of Φ25.4mm, and the thermal conductivity coefficient (unit W / M·K) is tested by a constant heat flow measurement device.
[0083] 5. Phase change temperature: The phase change latent heat of the phase change film was tested using a differential scanning calorimeter (DSC) at 25°C-100°C and a heating rate of 5K / min.
[0084] 6. Flame retardancy: The phase change film was punched into samples with a diameter of 13 mm × 125 mm, and the flame retardancy was tested according to the UL94 standard.
[0085] The main formula of raw materials and performance test results of Examples 1-5 are shown in Table 1 below:
[0086] Table 1
[0087]
[0088]
[0089] The main formulas of the raw materials and the test results of Comparative Examples 1-5 are shown in Table 2 below:
[0090] Table 2
[0091]
[0092]
[0093] Among them, the evaluation method of comprehensive evaluation is as follows:
[0094] Excellent means: peel force less than 5N / 25mm, flame retardant VTM-0, breakdown> 20KV, thermal conductivity ≥ 1.5W / m*K;
[0095] Poor: peel force <5N / 25mm, flame retardant VTM-2, breakdown <20KV, thermal conductivity ≤1.5W / m*K.
[0096] From the results in Table 1 and Table 2, we can see that:
[0097] The insulating thermally conductive adhesive film prepared in the embodiment of the present invention has excellent bonding, insulation, thermal conductivity, flame retardancy and weather resistance. The insulating film prepared thereby can not only improve the insulation of the liquid cooling plate, but also has certain phase change heat absorption and heat release characteristics.
[0098] In Comparative Example 1, there is too much phase change material, the prepared sample has poor heat resistance, and there are bubbles at high temperature; in Comparative Example 2, the diluent content is high, and the material bonding strength is insufficient; in Comparative Example 3, there is too little phase change material, and the latent heat of phase change is small; in Comparative Example 4, the thermal conductive filler is low, the thermal conductivity of the material is low, and the flame retardant performance is poor; in Comparative Example 5, the epoxy resin is too high, and no coupling agent is added, the material compatibility is low, the phase change material and the thermal conductive material are added less, and the latent heat is low.
[0099] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A phase change insulating film, characterized in that: The phase change encapsulation coating liquid is obtained by coating, drying and curing, wherein the phase change encapsulation coating liquid includes the following raw material components in parts by weight: 30-50 parts of epoxy resin, 1-20 parts of multifunctional glycidyl ether diluent, 3-5.5 parts of curing agent, 0.05-0.2 parts of accelerator, 0.05-0.2 parts of coupling agent, 20-30 parts of oil-absorbing filler, 5-15 parts of thermal conductive filler, 15-25 parts of phase change material, and 0.5-2 parts of flame retardant.
2. The phase change insulating film according to claim 1, characterized in that: The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, distyrene epoxy resin, biphenyl epoxy resin, polyether modified epoxy resin and polyurethane modified epoxy resin.
3. The phase change insulating film according to claim 1, characterized in that: The multifunctional glycidyl ether diluent is selected from at least one of benzyl glycidyl ether, phenyl glycidyl ether, polyethylene glycol glycidyl ether and polypropylene glycol glycidyl ether.
4. The phase change insulating film according to claim 1, characterized in that: The oil-absorbing filler is in powder or granular form, and its material is one or more of graphite, expanded graphite, graphene, graphene oxide, carbon nanotubes, and silicon carbide; The thermal conductive filler is one or a mixture of magnesium oxide, beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, crystalline silicon dioxide, and silicon carbide; The phase change material is one or more of paraffin, organic acid and sugar alcohol.
5. The phase change insulating film according to claim 1, characterized in that: The curing agent is any one of a latent amine curing agent, a phenolic curing agent and an acid anhydride curing agent or a mixture of at least two thereof; the latent amine curing agent is any one of dicyandiamide, aromatic amine, diaminodiphenylmethane and diaminodiphenyl sulfone or a mixture of at least two thereof; the acid anhydride curing agent is an acid anhydride having an aromatic skeleton and a hydride or a modified substance thereof and / or an acid anhydride having an alicyclic skeleton and a hydride or a modified substance thereof; The accelerator is any one of urea derivatives, imidazole and its derivatives, acetylacetone metal salts, triorganophosphine compounds, quaternary ammonium salts and fluoroborates, or a mixture of at least two of them; the urea derivative is any one of 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-p-nitrophenyl-1,1-dimethylurea, N-(3,4-dichlorophenyl)-N,N′-diphenylurea, 4-phenyl-1,1-dimethylaminourea, or a mixture of at least two of them.
6. The phase change insulating film according to claim 1, characterized in that: The coupling agent is any one of a titanate coupling agent, an aluminate coupling agent, an organic silane coupling agent, an organic chromium compound coupling agent and a borate coupling agent, or a mixture of at least two thereof; The titanate coupling agent is any one of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, 3-glycidyloxypropyl trimethoxy silane (KBM-403), isopropyl tris(dioctyl phosphate acyloxy) titanate, isopropyl dioleyloxy (dioctyl phosphate acyloxy) titanate, monoalkoxy unsaturated fatty acid titanate, bis(dioctyl pyrophosphate) ethylene titanate and triethanolamine chelate, bis(dioctyl pyrophosphate) ethylene titanate, γ-glycidyloxypropyl trimethoxy silane (KH-560) or a mixture of at least two thereof; The flame retardant is any one of a phosphorus flame retardant, a nitrogen flame retardant, a silicon flame retardant, a metal hydroxide flame retardant, a metal oxide flame retardant and a metal boride flame retardant, or a mixture of at least two thereof; The phosphorus-based flame retardant is any one of an organic phosphide, an organic phosphonate and a phosphite, or a mixture of at least two thereof; The organic phosphonate is any one of condensation-type halogen-free phosphate, tricresyl phosphate, triphenyl phosphate, tricresyl phosphate, butylbenzene phosphate, propylbenzene phosphate, phenoxy polyphosphazene, dimethyl methylphosphonate, diethyl ethylphosphonate, isopropylphenyl phosphate, tert-butylbenzene diyl phosphate, tetraarylarylene bisphosphate, resorcinol phosphate, tetraphenyl bisphenol A-diphosphate and pentaerythritol melamine phosphate, or a mixture of at least two thereof.
7. A method for preparing a phase change insulating film according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) adding the phase change material into a container, heating it to 80-100° C., adding the oil-absorbing filler under stirring, mixing evenly, then cooling it to room temperature, and then ball-milling the resulting mixture to obtain an intermediate composite material; 2) adding epoxy resin, multifunctional glycidyl ether diluent, thermal conductive filler, coupling agent, curing agent, accelerator and flame retardant into the solvent and mixing evenly to obtain a support layer material; 3) adding the intermediate composite material to the supporting layer material and stirring evenly to obtain a phase change encapsulation coating liquid; 4) The phase change encapsulation coating liquid is applied to the surface of the substrate layer, and heated and dried at 70-100° C. for 2-10 minutes, and a release film is attached to the surface of the formed phase change adhesive film to obtain the phase change insulating film.
8. The phase change insulating film according to claim 6, characterized in that: in, The oil-absorbing filler is expanded graphite, which is pretreated with a coupling agent KH560 before use. The pretreatment method is as follows: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and continuously stirred for 30 minutes to fully hydrolyze the coupling agent, and then boron nitride and expanded graphite are added, stirred for 3 hours, and then vacuum filtered, and dried in a 100°C oven for 2 hours to obtain pretreated graphite and boron nitride materials; Among them, the thermal conductive filler is boron nitride, which is pretreated with a coupling agent KH560 before use. The pretreatment method is: butanone and a dilute hydrochloric acid solution with a pH of 3 are mixed in a ratio of 9:1, 1% KH560 is added to the mixed solution, and the mixture is heated in a 50°C water bath and continuously stirred for 30 minutes to allow the coupling agent to be fully hydrolyzed, and then boron nitride and expanded graphite are added, stirred for 3 hours, and then vacuum filtered, and dried in an oven at 100°C for 2 hours to obtain pretreated graphite and boron nitride materials.
9. The phase change insulating film according to claim 7, characterized in that: in, The epoxy resin is E44 bisphenol A epoxy resin, the multifunctional glycidyl ether resin diluent is polypropylene glycol glycidyl ether, the curing agent is dicyandiamide, the accelerator is imidazole, the coupling agent is KH560, the phase change material is paraffin, and the flame retardant is triphenyl phosphate.
10. A liquid cooling plate, characterized in that: It is prepared by the following method: tearing off the release film on the phase change insulating film prepared by the method described in any one of claims 7 to 9, and then using a 100°C hot stick to adhere the phase change adhesive film to the surface of the water-cooled plate at 0.1-0.5MPa, and baking it in a 180°C oven for 30 minutes to obtain the liquid cooling plate.